LEXICAL TOOLS FORMING THE ARTISTIC TEXT: HOMONYMS - G. A. Kholboeva; M. Anorboeva (Academia Science Repository, 2023)
This article provides information about the methods of using homonyms from lexical tools to express the sound structure of the Uzbek language and written speech in the native language and reading literacy classes of elementary school students. It is known that primary education is an important stage in the continuous education system. Teaching the mother tongue takes the main place in it. In addition to the development of the main types of speech activity in students, mother tongue education in primary grades aims to solve the following important issues:The content of the knowledge given in the mother tongue in the elementary grades is about the sound structure of the Uzbek language and the ways of expressing sounds in written speech, about the change of words and the connection of words in a sentence, the morphemic composition of words and word formation, consists of knowledge about the lexical-semantic group of words, the correct writing rules of the Uzbek language and the use of punctuation marks. The given knowledge serves to develop students' speech. The lexical tools forming the artistic text have different characteristics. They mainly consist of homonyms, synonyms, antonyms, paronyms. These lexical tools are widely used in the 1st-2nd-3rd grade mother tongue reading literacy and 4th grade textbook texts. In this section of the work, we analyze the lexical tools and their specific features based on the ideas in the literature.